Sultan III. Murad İçin Hazırlanan Tarih-i Sultan Süleyman’ın (DCBL-T. 413) Tezhip Desenlerinin Çözümlemesi - Aracı, Nihal (International Balkan University, 2024)
The works prepared for the Ottoman sultans on various occasions made significant contributions to the development of book arts. One of these occasions is the works describing the wars, victories and important events during the reigns of the sultans. In this context, in the shahnāmah genre, which is one of the leading genres of historiography, valuable works have been produced not only in terms of the information it contains, but also in terms of its illustrations and illuminations. The subject of this article is the analysis of the illumination designs of the Tarih-i Sultan Süleyman with inventory T. 413 in the Chester Beatty Library in Dublin, which is a work prepared in this direction. In the introduction of the study, the preparation process of the works presented to the sultans and under whose patronage this process took place are mentioned. Subsequently, the cultural and artistic environment of the period of Sultan Murad III -as this work was prepared for him- is discussed and the effects of the concept of patronage in this context are tried to be explained. Afterwards, brief information is given about the institution of shahnāmah and the author of the work, Seyyid Lokman. In the following section, the illumination compositions of the work are analyzed. In the analysis in which the design setup is tried to be explained concisely, each decoration element is drawn in different colors and these drawings are placed side by side with the image. This layout plan is intended to enable a comparative reading. As a result of this analysis, in which the pattern setup and motif details are clearly seen, it has been tried to reveal the methods in which the design diversity is achieved in the triangle koltuk illumination.

Osmanlı sultanları için çeşitli vesilelerle hazırlanan eserler, kitap sanatlarının gelişimine mühim katkılar sunmuştur. Bu vesilelerden biri de sultanların saltanat dönemlerindeki savaşları, kazandıkları zaferleri, önemli olayları anlatan eserlerdir. Bu bağlamda, tarih yazıcılığının önde gelen çeşitlerinden olan şehnâme türünde, yalnızca içerdiği malumat bakımından değil, aynı zamanda resimleri ve tezhipleri itibariyle de çok kıymetli eserler verilmiştir. Makalenin konusunu da bu doğrultuda hazırlanmış bir eser olan ve Dublin Chester Beatty Kütüphanesi’nde bulunan T. 413 envanterli Tarih-i Sultan Süleyman’ın tezhip desenlerinin çözümlemeleri oluşturmaktadır. Çalışmanın giriş bölümünde, sultanlara takdim edilen eserlerin hazırlanış sürecine ve bu sürecin kimlerin hâmiliğinde gerçekleştiğine değinilmiştir. Devamında -mezkûr eserin kendisi için hazırlanması sebebiyle- Sultan III. Murad dönemi kültür-sanat ortamı ele alınmış ve hâmilik kavramının bu bağlamdaki etkileri anlatılmaya çalışılmıştır. Sonrasında şehnâmecilik kurumu ve çalışmanın konusu olan eserin müellifi Seyyid Lokman hakkında kısaca bilgi verilmiştir. Takip eden bölümde ise eserin tezhip kompozisyonlarının analizi yapılmıştır. Tasarım kurgusunun özlü bir şekilde anlatılmaya çalışıldığı söz konusu analizde, her bir bezeme unsuru ayrı renklerde çizilmiş ve bu çizimler görselle birlikte yan yana yerleştirilmiştir. Bu yerleşim planıyla karşılaştırmalı bir okuma yapılabilmesi hedeflenmiştir. Desen kurgusunun ve motif ayrıntılarının açık bir şekilde görüldüğü bu çözümleme neticesinde, üçgen koltuk tezhibinde tasarım çeşitliliğinin hangi yollarla elde edildiğine dâir yöntemler ortaya çıkarılmaya çalışılmıştır.
Analysis of Illumination Patterns of Tarih-i Sultan Süleyman (DCBL-T. 413) Prepared for Sultan Murad III
Keywords: Illumination; Design; Book Arts; Seyyid Lokman; Sultan Murad III; Shahnāmah; Tezhip; Tasarım; Kitap Sanatları; Şehnâme